The Tragic Vision The Confrontation of Extremity - Krieger, Murray (Johns Hopkins University Press, 2019)
Originally published in 1973. Literary critics who have studied tragedy and the tragic vision failed, in Murray Krieger's estimation, to define exactly what they saw as the tragic vision in general terms. An aim of his book is to create a tentative definition of tragic and to flesh out what the author sees as the definition most illuminating of modern literature and the modern mind. In order to do this, Krieger distinguishes between what he sees as the "tragic vision" and "tragedy"-tragedy, from his perspective, is an object's literary form, whereas tragic vision refers to a subject's psychology, the subject's view and version of reality. In light of the shriveling of the tragic concept in the modern world and the reduction of a total view to the psychology of the protagonist, Krieger contends that the protagonist in a tragedy is now more appropriately designated a "tragic visionary" than a "tragic hero."